Informed consent in medical practice: factors associated to its acquaintance in Peruvian physicians - Zavala, Salomón (2010)
Objectives: To identify factors associated to the informed consent acquaintance in Peruvian physicians. Design: Retrospective study, based in a comprehensive exam. Setting: Universidad Nacional Mayor de San Marcos. Participants: Physicians postulating medical specialization. Methods: A data base of 1 486 physicians applying to the 2009 residency program at San Marcos University who answered an informed consent acquaintance examination was used. Sex, age, university of origin and year of graduation were classified in two categories and the total score obtained in the examination in three categories, in order to procedure with bi and multivariate analysis. SPSS 15 program for chi square and multivaried analysis and Atlas ti program for comments qualitative analysis were used. Main outcome measures: Theoretical knowledge on informed consent. Results: Significant statistical differences in the frequency of correct answers by age, sex, university of origin and year of graduation were found. With multiva-ried analysis highest right scores were associated to being male, younger, graduated between 2004 and 2008, and graduated from San Marcos University. Conclusions: Theoretical knowledge on informed consent was better in younger physicians while their practical knowledge was better in physicians with more experience. Better score in correct answers in those graduated at San Marcos University would be related to better ethical training of their teachers and quality of medical students.